2019
DOI: 10.12998/wjcc.v7.i23.4150
|View full text |Cite
|
Sign up to set email alerts
|

Fatal complications in a patient with severe multi-space infections in the oral and maxillofacial head and neck regions: A case report

Abstract: BACKGROUNDOdontogenic infection is one of the common infectious diseases in oral and maxillofacial head and neck regions. Clinically, if early odontogenic infections such as acute periapical periodontitis, alveolar abscess, and pericoronitis of wisdom teeth are not treated timely, effectively and correctly, the infected tissue may spread up to the skull and brain, down to the thoracic cavity, abdominal cavity and other areas through the natural potential fascial space in the oral and maxillofacial head and nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…Treatment includes Co-amoxyclav 625 (Amoxicillin 500 mg ? Clavulanic acid 125 mg) thrice a day, Metronidazole 400 mg 3 times a day and Ibuprofen 400 mg 3 times a day [12][13][14].…”
Section: Application Of Telemedicine In Facio-odontogenic Pain Managementioning
confidence: 99%
See 1 more Smart Citation
“…Treatment includes Co-amoxyclav 625 (Amoxicillin 500 mg ? Clavulanic acid 125 mg) thrice a day, Metronidazole 400 mg 3 times a day and Ibuprofen 400 mg 3 times a day [12][13][14].…”
Section: Application Of Telemedicine In Facio-odontogenic Pain Managementioning
confidence: 99%
“…Non-life-threatening infections are generally not associated with fever and septicaemia. Treatment includes Co-amoxyclav 625 (Amoxicillin 500 mg + Clavulanic acid 125 mg) thrice a day, Metronidazole 400 mg 3 times a day and Ibuprofen 400 mg 3 times a day [ 12 14 ].…”
Section: Application Of Telemedicine In Facio-odontogenic Pain Managementioning
confidence: 99%
“…Dessa forma, Dai et al (2019), relatam que se essas infecções de origem dentária como periodontite periapical aguda, abscesso alveolar e pericoronarite não forem tratadas corretamente no seu estágio inicial, o processo infeccioso pode disseminar-se para outros órgãos, como o crânio, cérebro, cavidade torácica, cavidade abdominal. Portanto, essas infecções podem evoluir para complicações com risco de vida para o paciente, como infecção intracraniana, derrame pleural, empiema, sepse e até morte.…”
Section: Revisão De Literaturaunclassified
“…Humans are affected by various diseases involving the maxillofacial region, many including the odontogenic infections commonly encountered in hospital practice. These infections are difficult to detect by the clinician and at times lead to life-threatening complications[ 3 , 4 ]. Some authors have suggested that abscesses should be drained and cellulitis treated with antibiotics, but others have suggested draining for both.…”
Section: Introductionmentioning
confidence: 99%